2019
DOI: 10.1038/s41598-019-43901-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous sulfur on alleviating cadmium stress in tartary buckwheat

Abstract: Supplying exogenous sulfur-rich compounds increases the content of glutathione(GSH) and phytochelatins(PCs) in plant tissues, enabling plants to enhance their cellular defense capacity and/or compartmentalize Cadmium(Cd) into vacuoles. However, the mechanism by which surplus S modulates tolerance to Cd stress in different tissues need further investigation. In the present study, we found that supplementing the tartary buckwheat( Fagopyrum tararicum ) exposed to Cd with surplus S reversed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 41 publications
(73 reference statements)
5
44
0
Order By: Relevance
“…Reduced Cd accumulation in roots associated with a less tolerant Cd phenotype was also observed in the disruption lines of SULTR1;2 [51]. In addition to this, sulfate application increased Cd concentrations in the roots of wheat, mustard, and buckwheat plant [32,35,75]. However, these findings should be considered in relation to the general suggestion that the ability of plants to accumulate higher heavy metal levels in shoots rather than in roots is associated with a higher heavy metal tolerance [8].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Reduced Cd accumulation in roots associated with a less tolerant Cd phenotype was also observed in the disruption lines of SULTR1;2 [51]. In addition to this, sulfate application increased Cd concentrations in the roots of wheat, mustard, and buckwheat plant [32,35,75]. However, these findings should be considered in relation to the general suggestion that the ability of plants to accumulate higher heavy metal levels in shoots rather than in roots is associated with a higher heavy metal tolerance [8].…”
Section: Discussionmentioning
confidence: 68%
“…Cd exposure-induced synthesis of GSH and PC stimulates S assimilation by Cys, a major substrate for GSH synthesis [28][29][30][31]. Recent studies reported the close relation between sulfur availability and increased plant tolerance to Cd stress [32][33][34][35][36]. S assimilation in plants starts with the uptake of sulfate by the rhizosphere via sulfate transporters (SULTR) [30,31,37].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, S may have contrasting effects in crops. Low S content improves crop growth, whereas high S content limits nitrogen uptake, thereby diminishing crop production; hence, a proper level of S is vital [74]. Shi et al [73] found that the use of sodium sulfate enhances root Cd concentrations by up to 39%.…”
Section: Sulfur-based Fertilizersmentioning
confidence: 99%
“…Shi et al [73] found that the use of sodium sulfate enhances root Cd concentrations by up to 39%. Lu et al [74] indicated that enhancing Cd uptake via root vacuoles and reducing translocation in shoots under S-treated plants may be attributed to the increasing Cd binding on cell walls, chelation, and vacuolar sequestration with the support of nonprotein thiols, phytochelatins, and heavy metal ATPases in roots; it may also prevent the expression of transporters that support Cd translocation from roots to shoots.…”
Section: Sulfur-based Fertilizersmentioning
confidence: 99%
“…We can assume that higher Cd concentration (5 mg kg −1 DM) was toxic enough to block the processes involved in the transport of assimilates and ions to the seeds. Lu et al [56] observed a similar phenomenon in Fagopyrum tataricum. They stated that in plants exogenously treated with sulfur, increased Cd uptake in root vacuoles and its decreased translocation to the leaves can result from enhanced Cd binding by cell walls, chelation and vacuolar sequestration with nonprotein thiols, and inhibited transport of Cd from roots to shoots.…”
Section: Content In the Grainsmentioning
confidence: 68%